Leptin and TGF-β1 Downregulate PREP1 Expression in Human Adipose-Derived Mesenchymal Stem Cells and Mature Adipocytes - Bruno, Andreina; Di Sano, Caterina; Simon, Hans-Uwe; Chanez, Pascal; Patti, Angelo Maria; Di Vincenzo, Serena; Dino, Paola; D’Esposito, Vittoria; Formisano, Pietro; Beguinot, Francesco; Pace, Elisabetta (Frontiers in Cell and Developmental Biology, 2021)
Adipose tissue is widely recognized as an extremely active endocrine organ producing adipokines as leptin that bridge metabolism and immune system. Pre-B-cell leukemia homeobox (Pbx)-regulating protein-1 (PREP1) is a ubiquitous homeodomain transcription factor involved in the adipogenic differentiation and insulin-sensitivity processes. Leptin, as pleiotropic adipokine, and TGF-beta, known to be expressed by primary pre-adipocytes (ASCs) and mature differentiated adipocytes, modulate inflammatory responses. We aimed to assess for the first time if leptin and TGF-beta1 interfere with PREP1 expression in both ASCs and mature differentiated adipocytes. Human ASCs were isolated from subcutaneous adipose liposuction and, after expansion, fully differentiated to mature adipocytes. In both ASCs and adipocytes, leptin and TGF-beta1 significantly decreased the expression of PREP1, alone and following concurrent toll like receptor 4 (TLR4) activation. Moreover, in adipocytes, but not in ASCs, leptin increased TLR4 and IL-33 expression while TGF-beta1 enhanced TLR4 and IL-6 expression. Taken together, we provide evidence for a direct regulation of PREP1 by leptin and TGF-beta1 in ASCs and mature adipocytes. The effects of leptin and TGF-beta1 on immune receptors and cytokines, however, is limited to mature adipocytes, suggesting that modulating immune responses depends on the differentiation of ASCs. Further studies are needed to fully understand the regulation of PREP1 expression and its potential for the development of new therapeutic approaches in obesity-related diseases.